Some aspects of the internet usage for foreign languages teaching - Klimova, Olena; Cherednichenko, Galina (My University, 2011)
The article is devoted to the different approaches to the Internet as an education tool. The authors propose the practical illustration of saying that the technological resources must comply with the curriculum, not vice versa. The example of the Internet site usage for foreign languages teaching is given.
Keywords: internet; інтернет; интернет; education; approach; foreign languages; methods; освіта; підхід; іноземні мови; методи; образование; подход; иностранные языки; методы; кафедра ділової іноземної мови та міжнародної комунікації